A legal perspective on child support obligation after divorce: The Vietnamese case - Linh Thi My Nguyen; Giang Thi Truc Huynh; Qui Khac Tran (CTU Journal of Innovation and Sustainable Development)
Parents are legally obligated to pay child support; if they do not live with their child Upon divorce. The obligation to support the child following a divorce is a central provision of Viet Nam's 2014 Marriage and Family Act and a significant aspect of family law. It is the responsibility of both parents and the government to safeguard children. However, the 2014 Act on Marriage and Family still needs to improve its provisions regarding child support obligations, such as the absence of a minimum quantity and a starting date. This article investigates the historical periods and regulations governing child support obligations in Viet Nam compared to other nations. This study also evaluates the practical applicability of the current legal provisions and identifies their deficiencies. This study intends to recommend modifications to child support laws that will help protect children's rights following parental divorce.